A study on the endocrine disrupting effect of estrogenic compounds on the zebra mussel, (Dreissena polymorpha) : an in vivo/in vitro approach - Quinn, Michael Brian (Trinity College (Dublin, Ireland). Department of Zoology, 2002)
Endocrine disruption (ED) by environmental estrogens has become a major research area in environmental toxicology after the discovery that chemicals entering the environment had a feminising effect on exposed male animals. This phenomenon has been well studied in vertebrates particularly in fish, where the production of vitellogenin (Vtg), an egg yolk precursor protein normally only produced by females, by males has been developed as a biomarker of exposure to environmental estrogens. Despite they're ecological importance, little work has been carried out in invertebrates.
Keywords: Zoology, Ph.D.; Ph.D. Trinity College Dublin